A map of total longitudinal conductivity of the sedimentary cover of the Central Ukraine - Logvinov, I. M. (Reports of the National Academy of Sciences of Ukraine, 2015)
On the basis of summarizing the results of electric survey on DC, logging, and dimensional inversion of about 500 curves of magnetotelluric soundings, a map of the total longitudinal conductivity of surface deposits of the Central Ukraine from the northern border of Ukraine to the Western Black Sea Basin is constructed. The map makes it possible to evaluate the longitudinal resistance of the entire capacity of surface deposits. The results will be used in the design and the interpretation of geoelectric studies.